2014
DOI: 10.1103/physrevb.90.045124
|View full text |Cite
|
Sign up to set email alerts
|

Structural instability and the Mott-Peierls transition in a half-metallic hollandite :K2Cr8O16

Abstract: In order to explore the driving mechanism of the concomitant metal-insulator and structural transitions in quasi-one-dimensional hollandite K 2 Cr 8 O 16 , electronic structures and phonon properties are investigated by employing the ab initio density functional theory (DFT) calculations. We have found that the imaginary phonon frequency reflecting the structural instability appears only in the DFT + U (U : Coulomb correlation) calculation, which indicates that the Coulomb correlation plays an essential role i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 30 publications
1
6
1
Order By: Relevance
“…The calculated DOS in the metallic and insulating phases [Figs. 3(a) and 3(b), respectively] are quite similar to recent GGA þ U calculations with U ¼ 3 eV [15,17]. As is also observed in experimental VB spectra, the VB features of the calculated DOS seem very similar in the two phases, and no major changes are seen over large energy scales [Figs.…”
Section: B First-principles Band-structure Calculationssupporting
confidence: 85%
See 3 more Smart Citations
“…The calculated DOS in the metallic and insulating phases [Figs. 3(a) and 3(b), respectively] are quite similar to recent GGA þ U calculations with U ¼ 3 eV [15,17]. As is also observed in experimental VB spectra, the VB features of the calculated DOS seem very similar in the two phases, and no major changes are seen over large energy scales [Figs.…”
Section: B First-principles Band-structure Calculationssupporting
confidence: 85%
“…for the Cr 3þ and Cr 4þ states, the pinning of valence fluctuations suggests that the Peierls insulating phase most likely involves excitations of the type d nþ1 L 1 þ d nþ1 L 1 ↔ d nþ1 L 2 þ d nþ1 L 0 ; i.e., the charge fluctuations involve ligand holes, as was recently discussed for the nickelates[45]. Thus, while the Mott-Peierls picture describes spectral weight changes over large energy scales (about 1-2 eV), as has been discussed for the MIT in VO 2[18][19][20]46], and very recently, also for the MIT in related hollandites,K 2 V 8−x Ti x O 16[47], the present spectroscopy results with a low-energy-scale BCS-like T-dependent gap rule out a Mott-Peierls transition in K 2 Cr 8 O 16 , in contrast with such a proposition made in a very recent GGA þ U study[17]. Our results of K 2 Cr 8 O 16 are summarized in…”
contrasting
confidence: 61%
See 2 more Smart Citations
“…A separate GGA+U eff =3 eV based study identified a specific soft mode associated with this Peierls driven transition. 43 The situation for hollandite group manganese oxides under study here has been much less clear. Early studies of the parent α−MnO 2 showed antiferromagnetic order below 24.5 K. 44 Studies of K x Mn 8 O 16 with x near 1.5 showed a change in the activation energy associated with electrical conductivity around 200 K and changes in magnetic susceptibility at low temperature with some ambiguity as to the details of the ordering.…”
Section: Discussionmentioning
confidence: 90%